Evaluasi Pemekaran Wilayah di Indonesia: Studi Kasus Kabupaten Lahat - Khairullah Khairullah; Malik Cahyadin (Universitas Islam Indonesia, 2006)
This research aims to evaluate the concept and spatial pattern of regional expansion in Lahat District. The method in this research is deductive method and rationalistic approach. It adopts several techniques/guidelines from the existing regulations in order to consider comprehensively the spatial pattern in Lahat District. The research uses three major criteria, which are: physic/environment, economic and social in order to formulate spatial pattern of regional expansion. The analysis of of spatial pattern based on the physical/environmental criteria produces two regions of expansion, i.e. region I (9 sub-districts), and region II (10 sub-districts); the analysis on spatial analysis based on the economic criteria produces 2 regions, i.e. region I (8 sub-districts) and region II (11 sub-districts); the analysis on spatial pattern based on the social criteria produces 3 regions, i.e., region I (6 sub-districts), region II (6 sub-districts), and region III (7 sub-districts); the analysis on the combination of three criteria (physical/environmental, economic, and social criteria) in the overlay produces 2 regions, i.e., region I (8 sub-districts) and region II (11 districts); the analysis on comparison based on the analysis of spatial pattern which regards the physical/environment, economic and social criteria indicates that the policy has more weaknesses than the research result.Keywords: regional expansion, spatial pattern, policy analysis, Lahat Distric.